SPECIFICATION FORMALIZATION OF STATE CHARTS FOR COMPLEX SYSTEM MANAGEMENT - Nikitin, Dmytro (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2023)
This article presents a formalization approach for the requirements of object-oriented programs with state machines, using a spacecraft control system as a case study. It proposes a state pattern implementation, where each state is represented as a class with clearly defined responsibilities, and the transitions between states are controlled by the state objects themselves. Additionally, the application of model checking, theorem proving, and code generation techniques are discussed. The effectiveness of the proposed approach in ensuring compliance with the specified requirements is demonstrated, while also identifying potential drawbacks and limitations of the approach. The implementation is validated using a range of formal verification techniques, including model checking and theorem proving. The article also discusses how the approach can be extended and applied to other complex systems. Overall, the valuable insights into the formalization of requirements for object-oriented programs with state machines are provided, offering a practical and effective approach for verifying the correctness and completeness of such implementations. The results of this work have important implications for the development of safety-critical systems and can potentially improve the quality and reliability of software systems in various domains. By using mathematical models and rigorous formal methods, it is possible to detect and eliminate errors early in the development process, leading to higher confidence in the correctness of the final product. Future research in this area could explore the use of more advanced techniques, such as model-driven development and automatic code synthesis, to further streamline the software development process. Additionally, the development of more efficient and user-friendly tools could make these techniques more accessible to a wider range of developers and organizations. Altogether, the combination of formal methods and software engineering has the potential to revolutionize the way software systems are designed, developed, and verified, leading to safer and more reliable software for critical applications.